Life expectancy inequalities in Wales before COVID-19: an exploration of current contributions by age and cause of death and changes between 2002 and 2018. (April 2021) - Currie, J.; Boyce, T.; Evans, L.; Luker, M.; Senior, S.; Hartt, M.; Cottrell, S.; Lester, N.; Huws, D.; Humphreys, C.; Little, K.; Adekanmbi, V.; et al.
Abstract: Objectives: The COVID-19 pandemic in Wales and the UK has highlighted significant and historic inequalities in health between social groups. To better understand the composition of these inequalities and inform planning after the pandemic, we undertook a decomposition of life expectancy inequalities between the most and least deprived quintiles for men and women by age and cause of death and explored trends between 2002 and 2018. Study design: Statistical decomposition of life expectancy inequalities by age and cause of death using routine population mortality datasets. Methods: We used routine statistics from the Office for National Statistics for the period 2002–2018 on population and deaths in Wales stratified by age, gender, Welsh Index of Multiple Deprivation (WIMD) 2019 quintile and cause of death, categorised by International Classification of Disease, version 10, code into 15 categories of public health relevance. We aggregated data to 3-year rolling figures to account for low numbers of events in some groups annually. Next, we estimated life expectancy at birth by quintile, gender and period using life table methods. Lastly, we performed a decomposition analysis using the Arriaga method to identify the specific disease categories and ages at which excess deaths occur in more disadvantaged areas to highlight potential areas for action. Results: Life expectancy inequalities between the most and least WIMD quintiles rose for both genders between 2002 and 2018: from 4.69 to 6.02 years for women (an increase of 1.33 years) and from 6.34 to 7.42 years for men (an increase of 1.08 years). Exploratory analysis of these trends suggested that the following were most influential for women: respiratory disease (1.50 years), cancers (1.36 years), circulatory disease (1.35 years) and digestive disease (0.51 years). For men, the gap was driven by circulatory disease (2.01 years), cancers (1.39 years), respiratory disease (1.25 years), digestive disease (0.79 years), drug- and alcohol-related conditions (0.54 years) and external causes (0.54 years). Contributions for women from respiratory disease, cancers, dementia and drug- and alcohol-related conditions appeared to be increasing, while among men, there were rising contributions from respiratory, digestive and circulatory disease. Conclusions: Life expectancy inequalities in Wales remain wide and have been increasing, particularly among women, with indications of worsening trends since 2010 following the introduction of fiscal austerity. As agencies recover from the pandemic, these findings should be considered alongside any resumption of services in Wales or future health and public policy. Article in a Tweet: Growth in life expectancy in Wales was significantly slowing before COVID-19 following policies of austerity that began around 2010. People living in more deprived areas saw year-on-year worsening life expectancy trends for four of the most recent periods with available data. This study identifies key conditions and age groups driving the gap in life expectancy in Wales before COVID-19. Our analysis highlights key areas for action to consider in any recovery programme for Wales to build a fairer society and one more resilient to future infectious disease pandemics.